ANALISIS HUKUM MENGENAI PERLINDUNGAN ANAK DALAM PERSPEKTIF HAK ASASI MANUSIA (HAM) DI KABUPATEN TOPOYO - Umar Umar; Basyarudin Basyarudin (Lembaga Pendidikan dan Penelitian Manggala Institute, 2025)
This scientific work aims to determine the form of legal protection for children from a human rights perspective in Topoyo Regency. This type of research uses qualitative research with field data as the primary data source, especially the results of interviews and field observations at the Topoyo Regency Civil Service Unit Secretariat. Based on the results of this research, according to the Human Rights perspective, legal protection for children is an effort made by parents, government and society to fulfill and guarantee all children's rights guaranteed in the Convention on the Rights of the Child and Law Number 35 of 2014 concerning Protection. Child. According to a human rights perspective, legal protection for children is not being implemented because the government has not fulfilled its duty to protect children. The happiness of children is happiness together, and the happiness that is protected is happiness that protects. Children don't worry because their protection is done well, and they feel safe. Parents, families, communities, governments and countries benefit from children's welfare